European energy policy: Meeting the security of supply and climate change challenges - Dieter Helm (EIB Papers, 2007)
The paper critiques current European energy policy. The key market failures are identified and the reasons for intervention set out. In addition to the traditional concerns with monopoly and market failures, the public goods aspects of diversity and security of supply, together with environmental failures are highlighted. Whilst in the 1980s and 1990s, market power dominated in the context of excess supply, the new priorities of security of supply and climate change require new policy instruments - notably network interconnection, capacity markets, strategic storage, and enhancements to the EU Emissions Trading Scheme. The paper sets out the necessary reforms, together with the institutional structures at the EU level which would provide credibility.
Keywords: 330; EU-Energiepolitik; Energieversorgung; Klimaveränderung; EU-Staaten